A Synthesis Method of MnO2/Activated Carbon Composite for Electrochemical Supercapacitors. Issue 8 (5th June 2015) - Wang, Jia-Wei; Chen, Ya; Chen, Bai-Zhen
Abstract : In this paper, a MnO2 /activated carbon (AC) composite with high electrochemical performance is synthesized through a novel synthesis method (Grafting Oxidation Method). The structure and morphology are analyzed using X-ray diffraction, Fourier transmission infrared spectra, scanning electron microscopy and transmission electron microscopy. Additionally, the electrochemical properties are evaluated through cyclic voltammetry, electrochemical impedance spectra and galvanostatic cycling measurements. The results demonstrate this MnO2 /AC composite owes homogeneous particle size of nanometer dimension. The quasi-rectangular and symmetric cyclic voltammetry curves of the composite, which are measured under a three-electrode electrochemical system with a 0.5 mol L −1 Na2 SO4 solution at room temperature, indicate it has an ability of rapidly reversible Faraday reaction and good electrochemical behavior. Compared to the MnO2 /AC prepared through liquid-phase method, the composite prepared by grafting oxidation method exhibits a much higher specific capacitance which is up to 332.6 F g −1 at scanning rate of 2 mV s −1 . A laboratory capacitor assembled with this MnO2 /AC composite electrode shows an average capacitance attenuation rate of just 0.0068% after 2000 cycles. Besides, the impedance tests results show that the charge transfer resistance of this composite is 0.92 Ω, which is much lower than the composite (2.52 Ω) synthesized through liquid-phase method.